Socio-demographic variables predictors of knowledge attitude and behaviour of undergraduates in reproductive health and HIV prevention (2012)
Reproductive health problems and HIV and AIDS continue to be -a major public health problem affecting mostly the youths. Consequently. Various interventions have been used to reach young people with the aim of preventing the spread of HIV. The purpose of this study is to find out the contributions of undergraduate students' demographic variables In facilitating their knowledge of reproductive health including HIV and AIDS issues, change in attitudes and behaviour towards the prevention of HIV. A sample of 1,036 undergraduates, 548 male and 488 female students was involved in the study. The sample was drawn from three old generation federal universities located in the south-west, Nigeria. An instrument which compried of four Sections was used to collect data for the study. Regression analysis wasused to analyse the data collected, and multiple regression analysis of variance (ANOVA) . Beta weights and t-test were used to test the level of significance. The six socio-demographic variables (course of study, level, marital status, age, religion, gender) jointly account for 6% of the total variance in undergraduates' knowledge of reproductive health, HIV prevention issues, Attitudes and behaviours. Course of Study, marital status, Attitudes and behaviours. Course of study, marital status and age of respondents contributed significantly to undergraduates' knowledge of reproductive health including HIV and AIDS issues, change in attitudes and behaviour towards HIV prevention.